A study on erosion of soft sediment deposits - Zawawi Samba Mohamed,; Mahbubur Rahman,; Jamal Mohd Amin, (1997)
Erosional pattern of fine cohesive sediment must be defined to predict the transport model in estuarial water Resistance to erosion is largely dependent on physicochemical properties of sediment and fluid, as well as the interparticle bond which is characterized by shear strength. Successively incremental flow-induced bed shear stress is applied to initiate layer by layer erosion of soft cohesive sediment deposit to determine the rate of erosion. A decrease in erosion rate is observed at the end of each time step. This behavior is due to the increasing shear strength with depth. The rate of erosion was found to vary exponentially with cubic root of excess bed shear stress